Scaling agricultural innovations – How to manage institutional change? Key messages from the CGIAR++ Scaling Workshop, Hanoi 2018 - Koerner, Jana; Woltering, Lennart; Uhlenbrock, Silke; Ohmstedt, Uwe; Zeiske, Felix; Sartas, Murat; Theissen, Arne H. (2019)
In the occasion of the Conference on Scaling in Hanoi, November 2018, researchers of nine CGIAR++ centers and partners came together in a Workshop on Scaling, to explore ways for institutionalizing scaling efforts in their respective organizations. The key messages summarized in this Info Note shall help the wider scaling community – as individuals or organizations - to embrace and manage institutional change.